THE SIGNIFICANCE OF KIM TAE WONâS SONG LYRICS: A STUDY OF RIFFATERREâS SEMIOTICS - , HANIEF LINTANG NISITA; , Amin Basuki, S.S, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
ìë²½ This research is aimed to revealling the significance of Kim Tae Wonâs song lyrics. The song lyrics are taken from BooHwalâs eighth album, â (Saebyeok)â. This research only uses three out of eleven song lyrics, which are âë¹ì ë¹ì ì ì´ì¼ê¸°(Biwa Dangsinui Iyagi)â, âìë²½(Saebyeok)â, âì²êµìì II(Cheongukeseo II)â. This research employed Riffaterreâs semiotics which include a sequence of stage, namely heuristic and hermenutic reading, matrix, model, variant, and hipogram. The results of the research indicate that the theme of the song lyrics is about someoneâs love journey. Those themes include memories of sadness, hope for meeting with the beloved, and separation due to death.Sadness of separation can not be avoided by two people in love.In the grief a deep longing was still felt from loved ones who left because the memories can nott be forgotten. That longing is the cause of emergence of a desire to meet the love ones. If the three themes were connected, it would have a central meaning, sadness in romance. Everyone may experience happiness from meeting and sadness because of the separation.